Incidence and Risk Factors of Admission Deep Vein Thrombosis in Patients With Traumatic Fracture: A Multicenter Retrospective Study - Zhang, Li; Liu, Xiaobing; Pang, Peng; Luo, Zhenguo; Cai, Wenbo; Li, Wangyang; Hao, Jianhong (Clinical and applied thrombosis/hemostasis, 2023)
To identify risk factors of admission deep vein thrombosis (DVT) in patients with traumatic fractures. Medical records of 1596 patients with traumatic fractures were reviewed. According to the ultrasound reports of the lower extremity veins, patients were assigned to the DVT or non-DVT group. Univariate and multivariate logistic regression analyses were used to identify the independent risk factors of DVT, and the receiver operating characteristic (ROC) curve was used to analyze the predictive value of the D-dimer level for DVT. DVT admission incidence was 20.67%. Statistically significant differences were revealed between the 2 groups in terms of age, sex, fracture site, presence of hypertension, coronary heart disease, stroke, smoking status, time from injury to admission, and levels of fasting blood glucose, hemoglobin, fibrinogen, D-dimer, and hematocrit. Multivariate analysis results showed that age above 50 years, female, above-knee fracture, cigarette smoking, injury-to-admission delay beyond 48 h, low hemoglobin levels, high fasting blood glucose levels, and high D-dimer levels were independent risk factors for admission DVT. ROC analysis showed that the D-dimer level was effective for the prediction of admission DVT in patients with peri-knee and below-knee fractures (area under the curve [AUC] = 0.7296, cutoff point = 1.21 mg/L). An age over 50 years, female, above-knee fracture, smoking, injury-to-admission delay beyond 48 h, decreased hemoglobin level, and increased fasting blood glucose and D-dimer levels were found to be potential independent risk factors for admission DVT. In patients with peri-knee and below-knee fractures, the plasma D-dimer level was effective in predicting admission DVT.